On the Problem of Mining the Web - for a Curriculum - Bonner, Richard F.; Mamchych, Tetyana I.; Malc, Iryna I. (Advanced Information Technologies for Management – AITM 2008, 2008)
We report a pilot project, which is to examine the plausibility of automated response of a professional curriculum to the professional market by adaptive mining of the Internet. In particular, the project shall prototype software for curricula in applied statistics, founded in computational learning theory. Its technical progress is reported elsewhere; here, we put it into a bigger picture of general curriculum considerations. We outline its background, sketch its learning domain, state its ultimate criterion for self-evaluation, share its theoretical framing, and observe some principal limitations of its interest to teaching.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 17-26